Computing with Time: Microarchitectural Weird Machines. - Benjamin, Thomas S.; Eitel, Jeffery A.; Elwell, Jesse; Evtyushkin, Dmitry; Ghosh, Abhrajit; Sapello, Angelo (Communications of the ACM, 2024)
This article focuses on the evaluation of the components that make up the authors’ microarchitectural weird machines—weird registers, weird gates, and weird circuits. This article is an accompanying piece to the full research article originally published in April 2021. Here, the authors define use cases for these machines in the context of program obfuscation with an in-depth look at the registers, gates, and circuits.